Tunable narrowband and broadband coexisting absorber enabled by a simple all-metal grating for sensing applications - Wang, Jianwei; Zhang, Ze; Lin, Zhiyan; Li, Hanting; Gao, Hua; Fan, Zhenjun; Liu, Haifeng (Frontiers in Physics, 2023)
We realize a tunable narrowband and broadband coexisting absorber based on a simple step-shaped all-metal grating structure. The absorber presents an ultra-narrow absorption band of 1.5 nm and a relatively broad absorption band of 29.8 nm, both with nearly 100% absorption in the infrared region. The mechanism underlying the dual-band perfect absorption is the interaction between two diffraction coupled surface plasmon polariton (SPP) modes with one of them modulated by a cavity resonance. Influences of structure parameters on the absorption performance are numerically investigated. It is found that the positions of the two perfect absorption peaks can be easily tuned both independently and together by changing the structural parameters. In addition, the designed grating structure presents excellent sensing performance with sensitivity and figure of merit as high as 2514 nm/RIU and 1600RIU -1 , respectively. The excellent sensing performance, flexible tenability and simple structure design endow this grating absorber with great potential in high-precision biochemical sensing applications.